INTERNALISASI NILAI ANTI BULLYING MELALUI PEMBELAJARAN AKIDAH AKHLAK PADA SISWA KELAS II DI MI - Khabibi, Muhammad Kharis; Ariga Bahrodin (LPPM STAI Muhammadiyah Probolinggo, 2025)
Bullying is a form of moral deviance that is frequently found at the elementary school level. Although some may consider it a normal occurrence, in reality, this behavior has significant negative impacts on students’ social and psychological development. Bullying can manifest as physical violence, hurtful words, or psychological pressure, usually carried out repeatedly by individuals or groups toward victims perceived as weaker, either physically or socially. Therefore, anti-bullying education needs to be implemented from an early age, one of which can be through Akidah Akhlak (Faith and Morals) learning. This study aims to describe the internalization process of anti-bullying values and to identify the supporting and inhibiting factors in Akidah Akhlak learning among second-grade students at MI Hidayatul Mubtadiin Ngudirejo, Jombang. The research employs a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The findings reveal that the internalization of values occurs through teacher role modeling, integration of values into teaching materials, and support from both the school environment and parents. Supporting factors include the active involvement of all school members, while inhibiting factors involve negative influences from outside the school, limited regulations, and students’ underdeveloped emotional regulation skills.